Regional warming and the thermal regimes of American crocodile nests in the Tempisque Basin, Costa Rica - Murray, Christopher M. (2016)
Spatial variation in global climate change makes population-specific responses to this enigmatic threat pertinent on a regional scale. Organisms with temperature-dependent sex determination (TSD) potentially possess a unique physiological susceptibility that threatens population viability if rapid environmental effects on sex ratios render populations non-viable. A heavily male-biased sex ratio for hatchling American crocodiles of the Tempisque Basin, Costa Rica requires assessment of how nest temperature affects sex determination at this site, how females might compensate for these effects when creating nests, and how current patterns of climate change might alter future sex ratios and survival in hatchling cohorts. We demonstrate high within-nest variation in temperature but predict a female bias at hatching based on nest temperatures quantified here. Further, our data suggest that egg size and metabolic heating associated with this factor outweighs microhabitat parameters and depth in influencing nest thermal regimes. Finally, we document regional warming in the Tempisque Basin over the last 15 years and project that further heating over the next 15 years will not yield hatchling sex ratios as male biased as those currently found at this site. Thus, we find no support for nest temperature or climate change as likely explanations for male-biased American crocodile (Crocodylus acutus) sex ratios in the Tempisque Basin.